A new method for recording the temporal pattern of stride during treadmill running - Gullstrand, L.; Nilsson, J. (Sports Engineering, 2009)
The aim of this study was to investigate the reliability of a new infrared light based method (IR40) for recording temporal stride patterns during treadmill running. The IR40 device, emitting a tight web of 40 infrared light beams 10 mm above the treadmill running surface, was compared to a previously validated electro-pneumatic contact shoe (CS) method while nine well-trained athletes ran at 2.8, 3.3, 3.9, 4.4, 5.0, and 5.6 m s-1. Disconnection and reconnection of the IR beams marked the stance phase. The sampling rate was 500 Hz for both methods. The stance phase duration was on average 11.5 (±8.4) ms longer with the IR40 than with the CS depending on earlier touch down (8.3 ± 6.2 ms) and delayed toe off (3.2 ± 5.3 ms) registrations. Significantly different stance phases were recorded between all velocities and for both methods. Thus, despite the fact that the IR40 systematically measured a somewhat longer stance phase duration than CS, the IR40 is nonetheless useful for temporal stride analysis during treadmill running.